Effects of sleep duration, perceived organisational support and personal resilience on anxiety in non-hospitalised residents during the COVID-19 pandemic: a survey study in Ningbo, China - Jingjing Ma; Yiqing Zhang; Qihang Xu; Yuezheng Rong; Shunshun Lu; Zhengzheng Wang (BMJ Open)
Objective This study assessed the association between sleep duration, perceived organisational support (POS), personal resilience and anxiety among non-hospitalised residents during the COVID-19 pandemic in Ningbo, China.Methods In this cross-sectional study, an online survey was conducted from 27 January 2023 to 5 February 2023, involving non-hospitalised residents over 14 years old in Ningbo. We received 1938 valid responses. The study used the General Demographic Characteristics Scale, the Generalised Anxiety Disorder Scale, Brief Resilient Coping Scale and the POS questionnaire.Results Among the 1938 valid questionnaires, 1068 (55.1%) participants reported anxiety. Multivariate logistic regression analysis revealed that high organisational support (β=–0.34, adjusted OR (aOR) 0.71, 95% CI 0.51 to 0.98, p=0.038), moderate resilience (β=–0.26, aOR 0.77, 95% CI 0.63 to 0.95, p=0.013), high resilience (β=–0.67, aOR 0.51, 95% CI 0.36 to 0.73, p<0.001) and sleep duration of ≥7 hours (β=–1.00, aOR 0.37, 95% CI 0.28 to 0.49, p<0.001) were significantly associated with anxiety. Participant characteristics were not associated with anxiety.Conclusions During the COVID-19 pandemic, organisational support, personal resilience and adequate sleep duration were associated with anxiety among non-hospitalised residents. These findings highlight the importance of increasing organisational support, implementing interventions that promote resilience and stress management, ensuring sufficient rest and sleep duration, and helping residents better manage anxiety.